THE EFFECT OF TALKING STICK STRATEGY ON STUDENTS’ SPEAKING ABILITY OF ASKING AND GIVING OPINIONS - Gerard (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study aims to examine the effect of the Talking Stick strategy on students' speaking ability, specifically in the areas of asking and giving opinions. The research was conducted with a group of students, focusing on their ability to express themselves in spoken English in an academic setting. The Talking Stick strategy, which involves using a physical object (the "stick") to regulate speaking turns during discussions, was implemented as a teaching method to encourage active participation and facilitate communication among students. A pre-test and post-test design were used to measure the improvement in students’ speaking skills before and after the intervention. Data analysis revealed that the Talking Stick strategy had a significant positive effect on students’ abilities to ask and give opinions effectively. This research contributes to the field of language teaching by demonstrating the potential of the Talking Stick as an interactive approach to enhancing speaking proficiency, especially in the context of opinion-based interactions. The findings suggest that this strategy can be a valuable tool for educators aiming to improve students’ oral communication skills